Mannose enhances intestinal immune barrier function and dextran sulfate sodium salt-induced colitis in mice by regulating intestinal microbiota - Yang, Yi; Ma, Qiming; Wang, Qingyu; Zhao, Lifeng; Liu, Hengshan; Chen, Yanjun (Frontiers in Immunology, 2024)
Background: Inflammatory bowel disease (IBD) greatly affects human quality of life. Mannose has been reported to be used to treat IBD, but the mechanism is currently unknown. Methods: C57/BL mice were used as research subjects, and the mouse acute colitis model was induced using dextran sulfate sodium salt (DSS). After oral administration of mannose, the body weights and disease activity index (DAI) scores of the mice were observed. The colon lengths, histopathological sections, fecal content microbial sequencing, colon epithelial inflammatory genes, and tight junction protein Occludin-1 expression levels were measured. We further used the feces of mice that had been orally administered mannose to perform fecal bacterial transplantation on the mice with DSS-induced colitis and detected the colitis-related indicators.Results: Oral administration of mannose increased body weights and colon lengths and reduced DAI scores in mice with DSS-induced colitis. In addition, it reduced the expression of colon inflammatory genes and the levels of serum inflammatory factors (TNF-α, IL-6, and IL-1β), further enhancing the expression level of the colonic Occludin-1 protein and alleviating the toxic response of DSS to the intestinal epithelium of the mice. In addition, gut microbial sequencing revealed that mannose increased the abundance and diversity of intestinal flora. Additionally, after using the feces of the mannose-treated mice to perform fecal bacterial transplantation on the mice with DSS-induced colitis, they showed the same phenotype as the mannose-treated mice, and both of them alleviated the intestinal toxic reaction induced by the DSS. It also reduced the expression of intestinal inflammatory genes (TNF-α, IL-6, and IL-1β) and enhanced the expression level of the colonic Occludin-1 protein.Conclusion: Mannose can treat DSS-induced colitis in mice, possibly by regulating intestinal microorganisms to enhance the intestinal immune barrier function and reduce the intestinal inflammatory response.